Adsorption induced enzyme denaturation: the role of polymer hydrophobicity in adsorption and denaturation of alpha-chymotrypsin on allyl glycidyl ether (AGE)-ethylene glycol dimethacrylate (EGDM) copolymers - Lahari, Challa; Jasti, Lakshmi Swarnalatha; Fadnavis, Nitin W.; Sontakke, Kalpana; Ingavle, Ganesh C.; Deokar, Sarika Babasaheb; Ponrathnam, Surendra (Langmuir, 2010)
Effects of changes in hydrophobicity of polymeric support oil structure and activity of alpha-chymotrypsin (E.C.3.4.21.1) have been studied with copolymers of allyl glycidyl ether (AGE) and ethylene glycol dimethacrylate (EGDM) with increasing molar ratio of EGDM to AGE (cross-link density 0.05 to 1.5). The enzyme is readily adsorbed front aqueous buffer at room temperature following Langmuir adsorption isotherms in unexpectedly large amounts (25% w/w). Relative hydrophobicity of the copolymers has been assessed by studying adsorption of naphthalene and Fmoc-methionine by the series of copolymers from aqueous solutions. Polymer hydrophobicity appears to increase linearly oil increasing cross-link density from 0.05 to 0.25. Further increase in cross-link density Causes a decrease in naphthalene binding but has little effect on binding of Fmoc-Met. Binding of alpha-chymotrypsin to these copolymers follow the trend for Fmoc-methionine binding, rather than naphthalene binding, indicating involvement of polar interactions along with hydrophobic interactions during binding of protein to the polymer. The adsorbed enzyme undergoes extensive denaturation (ca. 80%) with loss of both tertiary and secondary structure on contact with the copolymers as revealed by fluorescence, CID and Raman spectra of the adsorbed protein. Comparison of enzyme adsorption behavior with Eupergit C, macroporous Amberlite XAD-2, and XAD-7 Suggests that polar interactions of the EGDM ester functional groups with the protein play a significant role in enzyme denaturation.